The Internal Audit and Integrated Quality Management System (iQMS) Online Course 2024: a continuous professional development initiative for better implementation of QMS at the Faculty of Pharmacy, UiTM / Lim Siong Meng - Lim, Siong Meng (Faculty of Pharmacy, 2024)
The Faculty of Pharmacy, UiTM had recently organised the Internal Audit and Integrated Quality Management System (iQMS) Online Course 2024. A total of 13 participants, including the Head of Quality Unit, internal auditors and academic staff, had successfully completed the intensive online course, which was held from the 16th July 2024 to the 18th July 2024. This was a continuous professional development initiative to enhance the competency of internal auditors with the latest information on the iQMS, which is an amalgamation of ISO 9001:2015 and 4 areas of self-review report.